Evidence of Pain, Stress, and Fear of Humans During Tail Docking and the next four weeks in Piglets (Sus scrofa domesticus) - Tallet, Céline; Rakotomahandry, Marine; Herlemont, Sabine; Prunier, Armelle (Frontiers in Veterinary Science, 2019)
Tail docking is widely performed in pig farms to prevent tail biting. We investigated the consequences of this practice on behavioral indicators of pain and stress, and on the human-piglet relationship during lactation. Within 19 litters, piglets (1 to 3 days of age) were submitted on day 0 (D0) to docking with a cautery iron (D), sham-docking (S) or no docking (U). Piglets from the D and S groups were observed during the procedure (body movements and vocalizations) and just after, in isolation, during 20s for body, tail and ear postures as well as ear movements. Piglets from the three treatments were observed in their home pen after docking on D0 and D3 afternoon for body posture, tail posture and movements. Piglets from the D and U groups were observed on D6, D12, D19 and D26 in their home pen for oral behavior, body and tail posture. Tail damage and tear staining were scored on D5, D11, D18 and D25. A 5-min motionless human test was performed on D14. During the procedure, D piglets screamed more and with a higher intensity (P < 0.05) than S piglets (n = 48 to 50). Just after docking, D piglets held their ears in a posture perpendicular to the head-tail axis and changed their ear posture more often (P < 0.05). Between D6 and D26, D piglets kept their tail immobile (P < 0.001) and in a horizontal position (P < 0.01) more often than U piglets (n = 45 to 47). Between D11 and D25, U piglets had higher scores for tail damage and damage freshness than D piglets (0.09 < P < 0.02) whereas tear-stain score was similar. In the human test, D piglets interacted later with an unfamiliar human than U piglets (P = 0.01, n = 18/group). Present data indicate signs of acute pain and stress in piglets due to docking during the procedure itself and adverse consequences throughout lactation thereafter, including on their relationship with humans. On the other hand, the presence of tail lesions shows that undocked piglets are subject to more tail biting, even before weaning.